The in-situ properties of clay soil in Pekan using cone penetration test - Nur Zaki, Arbain (2010)
Construction project for civil structures always experience big challenges in order to ensure no conflict to the foundation. As we know, foundation is an important initial work in a construction of civil structure. if a foundation is not designed according to its requirement and properly, collapse to the building might be occurred. The construction of foundation needs to take account for the strength (bearing capacity) of the site area. Here, site investigation plays an important role. Through the results of site investigation, the choosing for suitable type of foundation can be accomplished. This study had covered important aspects towards the choosing of foundation for a building construction. The objectives of this study is to determine the parameters of soil at site study and to determine the soil profile for site study using the method of Piezocone's Cone Penetration Test. This method had been chosen as it is the most reliable method to obtain dynamic pore pressure parameter at site study among all site investigation method. Through this method, data obtained had been tabulated and graphs had been plotted. The conclusions obtained from these data are for the parameters; cone resistance is 12.07 MPa, sleeve friction is 0.06 MPa and dynamic pore pressure is 0.65 MPa. The site study (Pekan) also had been concluded to be classified in clays type of soil with clays-clayey to silty clay. From above data, further analysis and calculation to obtain the suitable foundation for clay type of soil can be proceed.